2001
DOI: 10.1177/1077559501006002002
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment in American Indian and Alaska Native Communities: Integrating Culture, History, and Public Health for Intervention and Prevention

Abstract: This article addresses child maltreatment intervention and prevention among American Indians and Alaska Natives. The authors argue that history and culture must be included as context and variables for developing and implementing prevention programs in Indian Country. They propose that the public health violence prevention model would benefit from incorporating tenets of the history and culture(s) of diverse groups, in this instance American Indians and Alaska Natives. The authors offer an approach that focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Finally, the present study identified perceived community caring as a strong protective factor for suicidal behaviour. This finding suggests that all suicide prevention programming should involve the participation and support of all significant community figures for youth including parents/guardians, other family, teachers, and peers (DeBruyn et al, 2001;Moran & Reaman, 2002).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the present study identified perceived community caring as a strong protective factor for suicidal behaviour. This finding suggests that all suicide prevention programming should involve the participation and support of all significant community figures for youth including parents/guardians, other family, teachers, and peers (DeBruyn et al, 2001;Moran & Reaman, 2002).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…A multi-component approach, including building awareness in youth around the detrimental effects of drugs and alcohol, teaching social and judgement skills, and improving self-esteem, might be most efficacious in these communities (Moran & Reaman, 2002). For reducing childhood maltreatment including abuse in American Indian/Alaska Native communities, culturally sensitive and integrative prevention and intervention efforts including violence awareness, parenting skills, and support groups to educate youth on how to prevent violence behaviour, have been proposed (DeBruyn, Chino, Serna, & Fullerton-Gleason, 2001). Finally, the present study identified perceived community caring as a strong protective factor for suicidal behaviour.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…However, evidencebased programs developed for the majority culture are often ill suited for the unique historical experiences and cultural diversity of AIAN communities. [40][41][42][43] Consequently, there has been a growing emphasis on the development of intervention and research methodologies specifically for use in AIAN communities. [44][45][46][47] Many of the resulting approaches allow for the acknowledgment of multigenerational historical trauma, including centuries of warfare and other overt violence toward AIAN people, forced relocation and assimilation, and anti-Indian government policies and legal actions.…”
Section: Cbpr In American Indian and Alaska Native Communitiesmentioning
confidence: 99%
“…Because the GCD community is marginalized, it could be helpful to have participants be a part of designing their own education and prevention programs (DeBruyn et al, 2001). Aid workers expressed a desire to have programming explicitly on CSA, while parents requested general parenting information.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers recommend that violence prevention programs among U.S. Native American populations consider child maltreatment at the phenomenological level and foster local ownership of prevention programs (DeBruyn et al, 2001).…”
Section: Culture and Child Sexual Abusementioning
confidence: 99%